Analysis of factors influencing the attitudes towards the elderly of nursing students based on empathy and end‐of‐life care: A cross‐sectional study - Jinchan Zhang; Yang Fu; Hongli Zhang; Tianwei Tang; Mei Yin; Lei Shi (Wiley, 2022)
Abstract Aim This study aimed to explore the factors associated with attitudes towards the older adults among nursing students, to clarify the impact of empathy and end‐of‐life care on the attitude of the older adults, and to provide a basis for the follow‐up of education courses related to older adults care and the training of older adults care talents. Design A cross‐sectional study. Methods A cross‐sectional survey on nursing students' knowledge and attitudes towards older adults was conducted from 24 December 2020-24 February 2021. The Chinese versions of the end‐of‐life Attitudes Scale, Jefferson Empathy Scale‐Nursing Version and Kogan Attitudes Scale for the Elderly were used for this cross‐sectional study. We used the purposive sampling method to conduct a questionnaire survey on nursing students at Heilongjiang Nursing College (n = 371, effective response rate: 64.52%). Results The average score of FATCOD‐B was 99.04 (7.71), and the score of C‐JSE‐HPS was 100.67 (12.90). The total average score of nursing students' attitudes towards older adults was 139.91 (15.79). The hierarchical regression analysis showed that education (β = −.125, p = .025) and personal experience (β = −.132, p = .008) correlated negatively with attitudes towards the older adults, while the end‐of‐life care (β = .140, p = .013) and empathy (β = .285, p < .001) correlated positively with attitudes towards the older adults. Conclusions Religion, end‐of‐life care and empathy were positively correlated with nursing students' attitudes towards older adults. It is necessary to set up end‐of‐life care, empathy and education related to the older adults, and combine a variety of training forms, increasing humanistic assessments and reducing the employment pressure on nursing students by relevant departments can improve their attitudes towards the older adults.